Developing an Intervention to Improve the Health Related Quality of Life in Children and Young People With Serious Parental Mental Illness - Gellatly, Judith; Bee, Penny; Kolade, Adekeye; Hunter, Diane; Gega, Lina; Callender, Craig; Hope, Holly; Abel, Kathryn M. (Frontiers in Psychiatry, 2019)
Introduction Children and adolescents living with parental mental illness (CAPRI) are at increased risk of behavioural, social and educational difficulties, mental and physical health problems and have poorer quality of life (QoL). Adverse outcomes can extend into adulthood but are not inevitable. Recent policy and stakeholder consultation recognise the urgent need for interventions that extend beyond objective, service-led measures of health. Systematic evidence synthesis has demonstrated a lack of evidence-based interventions for enhancing holistic, child-centred outcomes. We aimed to co-develop a manualised, community-based intervention to improve QoL in CAPRI. Precedence was given to the QoL domains that were prioritised by stakeholders and deemed feasible to modify within a health and social care context. We describe here the modelling phase of developing the intervention emphasising co-production activities with CAPRI, their families and professionals who support them. Methods Semi-structured interviews and focus groups with CAPRI (n=14), parents (n=7), and professionals from health, social and educational sectors (n=31) in the UK. Topic guides qualitatively explored participants prior experiences, unmet needs, perceived barriers and facilitators to receiving/delivering support, and their ideals for a new intervention. Findings were synthesised with existing research evidence and presented to a mixed panel of clinical academics and health and social care professionals. A consensus exercise was used to identify the preferred structure, format and content of the manualised intervention. Results An 8-week group intervention for 6-16 year olds and their parents, called Young SMILES, has been co-developed along with associated training materials for facilitators. Each session addresses an identified need, but is underpinned by cross-cutting themes pertaining to mental health literacy, parent-child communication and problem solving skills. Sessions are delivered by two trained facilitators and held in accessible and acceptable community locations weekly for two hours. Conclusion Young SMILES captures a broad age range and level of need for CAPRI and can be evaluated with quantifiable child-centred outcomes. In line with current policy directives, this is the first UK-based, multi-context intervention to improve QoL in this population. Implementation and referral mechanisms are currently being evaluated in a multi-site feasibility trial.